2018
DOI: 10.5603/cj.a2017.0136
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety disorders and stressful events in Takotsubo syndrome

Abstract: Background: Anxiety disorders are more common in Takotsubo syndrome (TS) than in acute coronary syndrome patients. The aim of this study was to investigate whether pre-existing anxiety disorders predispose to TS triggered by exclusively emotional stressful events. Methods: Triggering events were compared in 58 TS patients with and without pre-existing anxiety disorders; clinical, electrocardiographic and echocardiographic data were also collected. Results: Thirty-one (53%) patients had a previous history of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Even though there were methodological disparities in the way data were collected (retrospective data by review of medical records vs. prospective assessment by standardized questionnaire at hospitalization), life-time anxiety disorders might be hypothesized to have a role in TTS. Interestingly, a recent study (Lazzeroni et al, 2018) found that only patients with pre-existing anxiety disorders were at risk of TTS triggered by emotional stressful events. This finding may help to explain why only some patients experience a stressful event as trigger of TTS.…”
Section: Discussionmentioning
confidence: 99%
“…Even though there were methodological disparities in the way data were collected (retrospective data by review of medical records vs. prospective assessment by standardized questionnaire at hospitalization), life-time anxiety disorders might be hypothesized to have a role in TTS. Interestingly, a recent study (Lazzeroni et al, 2018) found that only patients with pre-existing anxiety disorders were at risk of TTS triggered by emotional stressful events. This finding may help to explain why only some patients experience a stressful event as trigger of TTS.…”
Section: Discussionmentioning
confidence: 99%
“…After an emotional stressful event, patients with anxiety can experience acute cardiac and vascular sympathetic hyper-activation. This autonomic dysfunction can make patients more susceptible to TS [12]. The prevalence of anxiety disorders in patients with TS has been reported as between 26% to 56% of patients [13].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an RTA was categorised as a traumatic physical disorder [12]. The distinction between emotional and physical triggers can be diffi cult, as physical disorders may also cause emotional stress.…”
Section: Discussionmentioning
confidence: 99%
“…The variables in our study include patient demographics (age, sex, race, household income, primary payer for the hospitalization) and hospital demographics (hospital type, hospital size and region). To further reduce selection bias, we included common cardiovascular comorbidities, such as smoking, hypertension, obstructive sleep apnea (OSA), peripheral artery disease (PAD), and other reported risk factors for TCM including chronic obstructive pulmonary disease (COPD), 21,22 anxiety 23 and depressive disorders, 18 obesity, 24 diabetes mellitus (DM), 25 chronic kidney disease (CKD) 26 and sepsis. 27 In-Hospital Outcomes…”
Section: Variablesmentioning
confidence: 99%